The effects of capital structure decisions on financial performance of insurance companies in Jordan - Almajali, Mohannad Ahmad Kamel
Capital structure is considered an essential corporate financial management context and is mainly related to the establishment of ideal debt policy. For insurance companies, this decision becomes more sensitive and that is because unique characteristic of the insurance industry is that its product is basically a promise. Unlike a physical product or even some other service, insurance firms must have adequate means of determining the appropriate amount of capital that is necessary to absorb unexpected losses arising from insurance claims. Therefore, the success of insurance firms Jordan's dynamic business environment depends on their ability to effectively determine the optimum and appropriate capital mix that is necessary to ensure that the shareholders get returns. Despite substantial theoretical developments in the field of corporate finance over the past several decades, the rift between theory and practice still needs to be reconciled. This study aims to examine the effect of capital structure on the financial performance of listed Insurance firms in Jordan. This study used the secondary data collected from the annual report of the nineteen insurance companies are listed on the Amman Stock Exchange from 2008-2017. The static panel data analysis technique is used to examine the effect of capital structure on insurance firm's performance. This study findings suggest that capital structure influence the performance of the listed insurance films in Jordan. The results also reveal a significantly positive relation between debt financing (long-term debt and short-term d bt and performance indicators, namely, return on assets (ROA), return on quity (ROE) and (Tobin's Q). While, equity financing has a significant positive relationship with return on equity (ROE), return on (ROA) and (Tobin's Q). These results are consistent with trade-off theory that assumes that companies usually are financed partly with debt and partly with equity, the trade-off theory states that the optimal capital structure is a trade-off between interest tax shields and cost of financial distress. Other findings indicate that the 'z® of the firm, age of the firm. sales growth, market concentration and inflation fate affect the performance of the insurance firm. Therefore, this study recommend that Jordanian insurance firms to diversify its sources of financing and not to rely significantly on debts financing, as the results prove that equity financing is a valuable source of funding, The outcomes of the study may guide entrepreneurs, loan- creditors an policy planners to formulate better policy decisions in respect of the mix of debt an equity capital and to exercise control over capital structure planning.